Effect of Pomegranate Peel Alone and in Combination with Rosiglitazone on Oxidative Stress and Insulin Levels in Type 2 Diabetic Rats (Medical Forum Monthly, 2024)
Objectives: To evaluate the effect of pomegranate peel extract with or without rosiglitazone on plasma malondialdehyde (MDA) and insulin levels in insulin resistant diabetic rats.Study Design: Randomized control trial studyPlace and Duration of Study: This study was conducted at the Department of Physiology, Army Medical College, Rawalpindi, in collaboration with National Institute of Health (N.I.H), Islamabad from 1st January 2011 to 28th May 2011.Materials and Methods: Type 2 diabetes mellitus was induced in sixty healthy rats. The diabetic rats were divided into four groups, namely diabetic control group which received intraperitoneal injection of normal saline daily, pomegranate group which was treated similar to control group and also received pomegranate peel extract (200mg/kg body weight) orally once daily, rosiglitazone group which received intraperitoneal injection of rosiglitazone (5mg/kg body weight) daily and the combined group received both pomegranate extract (100 mg/kg body weight, orally) and intraperitoneal injection of rosiglitazone (2.5 mg/kg body weight) daily for 28 days.Results: The plasma MDA levels were significantly (p< 0.001) reduced in pomegranate, rosiglitazone and combined groups respectively as compared to the diabetic control. The mean serum levels of insulin (p< 0.001) reduced in pomegranate group, in rosiglitazone group and in combined group respectively.Conclusion: Pomegranate peel extract is hypoglycemic and hypolipidemic agent in low doses when used alone or in combination with rosiglitazone in type 2 diabetic rats.